Self-propelled nanomotor reconstructs tumor microenvironment through synergistic hypoxia alleviation and glycolysis inhibition for promoted anti-metastasis - Wenqi Yu; Ruyi Lin; Xueqin He; Xiaotong Yang; Huilin Zhang; Chuan Hu; Rui Liu; Yuan Huang; Yi Qin; Huile Gao (Elsevier, 2021)
Solid tumors always exhibit local hypoxia, resulting in the high metastasis and inertness to chemotherapy. Reconstruction of hypoxic tumor microenvironment (TME) is considered a potential therapy compared to directly killing tumor cells. However, the insufficient oxygen delivery to deep tumor and the confronting "Warburg effect" compromise the efficacy of hypoxia alleviation. Herein, we construct a cascade enzyme-powered nanomotor (NM-si), which can simultaneously provide sufficient oxygen in deep tumor and inhibit the aerobic glycolysis to potentiate anti-metastasis in chemotherapy. Catalase (Cat) and glucose oxidase (GOx) are co-adsorbed on our previously reported CAuNCs@HA to form self-propelled nanomotor (NM), with hexokinase-2 (HK-2) siRNA further condensed (NM-si). The persistent production of oxygen bubbles from the cascade enzymatic reaction propels NM-si to move forward autonomously and in a controllable direction along H2O2 gradient towards deep tumor, with hypoxia successfully alleviated in the meantime. The autonomous movement also facilitates NM-si with lysosome escaping for efficient HK-2 knockdown to inhibit glycolysis. In vivo results demonstrated a promising anti-metastasis effect of commercially available albumin-bound paclitaxel (PTX@HSA) after pre-treated with NM-si for TME reconstruction. This cascade enzyme-powered nanomotor provides a potential prospect in reversing the hypoxic TME and metabolic pathway for reinforced anti-metastasis of chemotherapy.